Self-reported symptoms after induced and inhibited bronchoconstriction in athletes - Simpson, A.; Romer, L. M.; Kippelen, B. (Medicine & Science in Sports & Exercise, 2015)
Purpose: A change in the perception of respiratory symptoms after treatment with inhaled beta2 agonists is often used to aid diagnosis of exercise-induced bronchoconstriction (EIB). Our aim was to test the association between subjective ratings of respiratory symptoms and changes in airway caliber after induced and inhibited bronchoconstriction in athletes with EIB.